STUDI NUMERIK PENGURANGAN GAYA DRAG PIPA SILINDER PADA HEAT EXCHANGER DENGAN MENEMPATKAN PIPA SILINDER TIPE I-530 NUMERICAL INVESTIGATION OF DRAG FORCE REDUCTION ON THE HEAT EXCHANGER WITH PLACEMENT OF I-53â° TYPE CYLINDER - Verdian Kurniawan; Gunawan Sakti; Bambang Junipitoyo (Approach : Jurnal Teknologi Penerbangan, 2019)
This study is basic research that focused on reducing drag forces on a cylindrical pipe in a heat exchanger with the placement of a bluff body I-53â° type cylinder upstream of the main cylinder. The aerodynamic characteristics of the main cylinder and the cylinder with bluff body I-53â° cylinder type are modeled within 2D by using ANSYS FluentÂ® at the laminar flow.The drag-reducing is made on the geometry within diameter D = 60 mm, where the distance between the center to center of the cylinders is 1.2 â‰¤ s/D â‰¤ 1.4 and Reynolds number Re = 5.3 x 104 at free stream velocity =14 m/s. The numerical simulations using variations of the turbulent models k-epsilon (2eq), k-omega (2eq) dan transition k-kl-omega (3eq).The output of this study is expected to gain better aerodynamic performance by comparing some parameters in measure between a single-cylinder and a bluff body. The measured parameters analyzed are the coefficient of pressure, the pressure distribution around the main cylinder wall, the coefficient of lift, the coefficient of drag, and the visualization of the velocity and pressure contours.